Beware of broken windows! First impressions in public-good experiments - Martin Beckenkamp; Christoph Engel; Andreas Glöckner; Bernd Irlenbusch; Heike Hennig-Schmidt (Max Planck Institute for Research on Collective Goods, 2009)
Broken Windows: the metaphor has changed New York and Los Angeles. Yet it is far from undisputed whether the broken windows policy was causal for reducing crime. In a series of lab experiments we show that first impressions are indeed causal for cooperativeness in three different institutional environments: absent targeted sanctions; with decentralised punishment; with decentralised punishment qualified by the risk of counterpunishment. In all environments, the effect of first impressions cannot be explained with, but adds to, participants' initial level of benevolence. Mere impression management is not strong enough to stabilise cooperation though. It must be combined with some risk of sanctions.
Keywords: C91; D03; D63; H41; K14; K42; 330; Broken Windows; Impression Management; Criminal Policy; Public Good Experiment; Kriminalpolitik; Rechtsdurchsetzung; Öffentliches Gut; Test